Kendala Prosedural Pembentukan Peraturan Daerah dan Implikasinya terhadap Mekanisme Pengujian Yuridis: Studi Empiris pada Bapemperda DPRD Provinsi Jawa Barat - Aslan Noor; Johan Amanda Maliku; Alifia Cahyanda Septiani; Rafalina Oktatia; Fadhil Putra Nurizal (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
Regional Regulations (Perda) constitute a fundamental legal instrument in the administration of regional autonomy in Indonesia. This study aims to: (1) analyze the judicial review mechanism for laws that harm individuals or legal entities within Indonesia's constitutional system; (2) examine procedures for reviewing Government Regulations with implications for harm to individuals or legal entities; and (3) evaluate Perda formation procedures of the West Java Provincial Government and DPRD from the perspective of the State Administrative Court (PTUN). The study employs a normative-empirical method with a descriptive-analytical juridical-normative approach, supplemented by semi-structured interviews with representatives of Bapemperda DPRD West Java Province. Findings indicate that the Constitutional Court's judicial review mechanism is insufficiently responsive to individual remediation; judicial review of sub-statutory regulations by the Supreme Court is not optimally integrated with PTUN mechanisms; and Perda formation in West Java faces procedural constraints including budget limitations, shortage of legislative experts, inadequate substantive public participation, and institutional political dynamics. The theoretical implication affirms the need for incidental review reform within PTUN as a complement to judicial review.